Dental caries among 12-year-old children after discontinuation of water fluoridation in Pahang, Malaysia - Abdul Karim, Faizah; Mohd Yusof, Zamros Yuzadi; Mohd Nor, Nor Azlida (UI Scholars Hub, 2020)
Background: Water fluoridation (WF) has been a national caries prevention program in Malaysia since 1972. However, between July 2012 and December 2013, WF was discontinued in Pahang. This study aimed to compare caries prevalence and mean caries experience among Malaysian children in WF and WF-ceased areas and determine its associated risk factors. Methods: This cross-sectional study was conducted among 12-year-old schoolchildren in two Malaysian states: Pahang (WF-ceased) and Perak (WF-continued). Dental caries was examined using ICDAS criteria, and a questionnaire was used to collect relevant data. Associations between independent variables and dental caries were analyzed by simple logistic regression and general linear model analyses. Results: Dental caries (D4-6MFT) was significantly higher among children in WF-ceased areas than in communities where WF continued. Multivariate analysis demonstrated that exposure to WF remains a strong predictor of low caries experience among the study population. Moreover, children with irregular toothbrushing frequency before sleep and whose parents have lower educational attainment are associated with higher caries experience. Conclusion: Caries prevalence and mean caries experience were significantly higher among children in WF-ceased areas than in communities where WF continued. Multivariate analysis revealed that several factors were associated with caries experience.